Early Report of Red Root Rot of Ganoderma sp. on Agathis sp. (Damar) in Mount Walat Education Forest, Sukabumi, West Java - Elis Nina Herliyana (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2012)
Damar (Agathis spp.) is one type of forestry tree producing high-quality wood that is light colored and known as raw vinir. Damar tree has been planted in the Mount Walat forest Education (HPGW) IPB since 1963. The stands are grown in addition to being carbon stock and play a role in the balance of ecosystems, has also been a lot of produce Copal (resin) of value economically. However the current spread of the disease has been diagnosed of Red root rot by Ganoderma are feared to be sharpened and detrimental. This paper is an early report that needs serious attention. Research on the factors that favour the occurrence of epidemic diseases needs to be done. Due to the alternate host Ganoderma spp. on this sufficiently broad